Monte Carlo Simulation to Understand the Working Mechanism of The Electrolytes Lithium Hexafloorophosphate and Ethylene Carbonate - Ego Srivajawaty Sinaga; Hubertus Ngaderman (Jurusan Fisika FMIPA Universitas Andalas, 2026)
Monte Carlo (MC) simulations provide a powerful approach to investigate electrolyte–electrode interactions and to optimize battery design. This study aims to determine the entropy and average energy of a lithium salt–ethylene carbonate (EC) system, as these parameters are essential for evaluating the Boltzmann factor. The Boltzmann factor was derived from entropy concepts and the principle of maximum entropy, which involves the Boltzmann constant (k) and the number of accessible states (Ω). Simulations were performed using Lennard–Jones parameters within a canonical ensemble framework to compute entropy and energy for systems with varying atom numbers. Results show that the system entropy for two atom types (200 atoms) was 6.67 × 107 kJ·mol–1·K–1. For three atom types (300 atoms), the equilibrium entropy reached 1.1 × 1010 kJ·mol–1·K–1, and for four atom types (400 atoms), 1.3 × 1013 kJ·mol–1·K–1. When reduced to five atom types with only 300 atoms (to minimize computational cost), the entropy was 2.4 × 108 kJ·mol–1·K–1. The simulations, employing the Metropolis criterion, successfully identified globally stable configurations, providing new insights into entropy-driven behavior in lithium battery electrolytes.